Rules of Origin: Conceptual Explorations and Lessons from the Generalized System of Preferences - Teruo Ujiie (Asian Development Bank (ADB), 2006)
Customs valuation, commodity classification system, and rules of origin are the three basic customs laws. Rules to determine a country of origin, or "nationality" of a country of production of goods, are called "rules of origin." They are widely used in international trade in the application of different tariffs, trade remedy measures, tariff quotas, and trade statistics. With the globalization of economic activities resulting in outsourcing of materials as well as the global proliferation of free trade agreements, rules of origin have become one of the major trade issues among both public and private sectors. Rules of origin often result in the so-called "spaghetti-bowl" effect. Since there is no agreement on product-specific harmonized rules of origin, international trade - both preferential and nonpreferential - is governed by different national laws. This paper intends to describe key conceptual aspects of rules of origin, focusing on lessons learned on origin criteria under the Generalized System of Preferences as well as from the efforts of the World Customs Organization and World Trade Organization to harmonize different origin rules.
hdl:11540/1889
Keywords: 330